The Effectiveness of ThingLink in Teaching New Vocabulary to Non-Native Beginners of the Arabic Language - Roslan, Nur Najhah Akmal; Sahrir, Muhammad Sabri (IIUM Press, 2020)
Low proficiency in the Arabic language, specifically in vocabulary learning, has been a longstanding issue for non-native Arabic speakers. Traditional language pedagogy, such as chalk and talk and memorization, continues to be a widely-known cause of low proficiency that affects 21st century students. Thus, this study sought to investigate the effectiveness of using ThingLink, an interactive image annotation tool, as an intervention to teach Arabic vocabulary to beginners of the language at a public university in Malaysia. The study adopted a preexperimental design, i.e., the pretest-posttest one group design, involving 30 students who were beginners of Arabic. The Vocabulary Knowledge Scale (VKS) and a modified TAM questionnaire were utilized to examine ThingLink’s effectiveness in three aspects, i.e., perceived usefulness, perceived ease of use and students’ vocabulary achievement. The data were analyzed descriptively and with a paired samples t-test. The results showed a statistically significant increase in vocabulary achievement among the subjects, but the effect of the intervention was only moderate at Cohen’s d = 0.42. The subjects rated ThingLink positively on both usefulness and ease of use, although their endorsement of the app’s ease of use was higher than their rating of its usefulness. The subjects’ reactions to ThingLink indicate that it is an effective tool for language teachers and students to use. The results of the study support the use of ThingLink as language learning app capable of meeting the needs and goals of 21st century education.